Runoff characteristics and application of HEC-HMS for modelling stormflow hydrograph in an oil palm catchment - Yusop, Zulkifli; Chan, C. H.; Katimon, A. (IWA Publishing, 2007)
Rainfall-runoff processes in a small oil palm catchment (8.2 ha) in Johor, Malaysia were examined. Storm hydrographs show rapid responses to rainfall with a short time to peak. The estimated initial hydrologic loss for the oil palm catchment is 5 mm. Despite the low initial loss, the catchment exhibits a high proportion of baseflow, approximately 54% of the total runoff. On an event basis, the stormflow response factor and runoff coefficient ranges from 0.003 to 0.21, and 0.02 to 0.44, respectively. Peakflow and stormflow volume were moderately correlated with rainfall. The hydrographs were satisfactorily modelled using the Hydrologic Engineering Centre–Hydrologic Modelling System (HEC-HMS). The efficiency indexes of the calibration and validation exercises are 0.81 and 0.82, respectively. Based on these preliminary findings, it could be suggested that an oil palm plantation would be able to serve reasonably well in regulating basic hydrological functions.